Preparation and Characterization of Blood Substitutes Based on Amphiphilic Biodegradable Copolymers - Gao, Yanjun; Cai, Liying; Li, Yunhui; Gao, Ying; Yang, Xiuyun (Asian Journal of Chemistry, 2014)
A biodegradable hemoglobin nanoparticles based on the copolymers of MPEG-b-PLA was prepared by self-assemble. The optimization conditions were obtained that the hemoglobin was encapsulated in the polymersomes. The hemoglobin nanoparticles with different states encapsulated in the polymersomes can be mutual transformed under different gas atmosphere was observed by UV spectra. While the oxygen partial pressure was increased, the oxy-hemoglobin was gradually transformed from deoxy-hemoglobin.